HPLC-ESI-MS method for C60 fullerene mitochondrial content quantification - Anna Grebinyk (Data in Brief, 2018)
The presented dataset describes the quantification of carbon nanoparticle C60 fullerene accumulated in mitochondria of human leukemic cells treated with nanostructure. Firstly, the high performance liquid chromatography–electro spray ionization–mass spectrometry (HPLC-ESI-MS) method was developed for quantitative analysis of pristine C60 fullerene. Then, human leukemic cells were incubated with C60 fullerene, homogenized and subjected to the differential centrifugation to retrieve mitochondrial fraction. The C60 fullerene content was quantified by HPLC-ESI-MS in extracts of cellular fractions.This data article refers to the research article “C60 Fullerene Accumulation in Human Leukemic Cells and Perspectives of LED-mediated Photodynamic Therapy” by Grebinyk et al. [1].